Exploring new scaffolds for angiotensin II receptor antagonism. Issue 18 (15th September 2016) - Kritsi, Eftichia; Matsoukas, Minos-Timotheos; Potamitis, Constantinos; Karageorgos, Vlasios; Detsi, Anastasia; Magafa, Vasilliki; Liapakis, George; Mavromoustakos, Thomas; Zoumpoulakis, Panagiotis
Graphical abstract: Highlights: Ligand-based pharmacophore model & virtual screening for AT1 R antagonists. 4 hits were evaluated for their binding affinity, 3 were in μM range. One hit compound exhibited IC50 equal to 199 nM. Molecular Dynamics simulations may explain differences in activity. All hits share different scaffolds than commercial ARBs. Abstract: Nowadays, AT1 receptor (AT1 R) antagonists (ARBs) constitute the one of the most prevalent classes of antihypertensive drugs that modulate the renin-angiotensin system (RAS). Their main uses include also treatment of diabetic nephropathy (kidney damage due to diabetes) and congestive heart failure. Towards this direction, our study has been focused on the discovery of novel agents bearing different scaffolds which may evolve as a new class of AT1 receptor antagonists. To fulfill this aim, a combination of computational approaches and biological assays were implemented. Particularly, a pharmacophore model was established and served as a 3D search query to screen the ChEMBL15 database. The reliability and accuracy of virtual screening results were improved by using molecular docking studies. In total, 4 compounds with completely diverse chemical scaffolds from potential ARBs, were picked and tested for their binding affinity to AT1 receptor. Results revealed high nanomolar to micromolar affinity (IC50 ) for all the compounds. Especially, compound4 exhibited a binding affinity of 199 nM. Molecular dynamics simulations were utilized in an effort to provide a molecular basis of their binding to AT1 R in accordance to their biological activities.